Numerical Simulations of Groove Topography Effects on Film Thickness and Friction in EHL Regime - Touche, T.; Woloszynski, Tomasz; Podsiadlo, P.; Stachowiak, Gwidon; Cayer-Barrioz, J.; Mazuyer, D. (Springer, 2017)
© 2017, Springer Science+Business Media, LLC. The effects of depth and top width of transverse rectangular grooves on film thickness and friction in elastohydrodynamic lubrication (EHL) regime were investigated through numerical simulations. Results were obtained in the form of pressure profiles and Stribeck curves for central and minimum film thickness and for friction coefficient. The results indicate that grooves with narrow top widths reduce the minimum film thickness and that this reduction is greater for deeper grooves. Lubricant shearing inside these grooves was further identified as a dominant factor contributing to friction. Near the groove edges, however, no evidence of micro-EHL effect was observed. Based on the results, a groove volume parameter was proposed to characterise the groove lubrication efficiency. We found that the parameter was linearly related to the average central film thickness and by increasing the groove wavelength the film could be made thicker than that of a smooth contact.